Political and Institutional Dimension of the Chairman of the High Council Aqif Pasha Elbasani, 1920-1924 - Sherifi, Eldi (Richtmann Publishing, 2019)
Recognition of the intellectual, political and patriotic dimension of the members of the High Council, serves not only to recognize their real activity and contributions, but also to understand the political and institutional mentality of the elite of the time and the judgment and assessment they had of the activity of constitutional institutions. Recognition of members of the High Council has been and is limited. Whereas, the need to recognize them is not only a requirement for students of law faculties, but also for the academic staff of teaching in political and legal sciences that give lectures on the history of political institutions of the Albanian state, Constitutional Law, etc. Aqif Pasha Elbasani, Luigj BumÃ§i, Abdi Bej Toptani, and Dr. Mihal Turtulli were elected members of the High Council from the Lushnja Congress. While from 1920 when that institution was founded until 1925, when the Republic of Albania was founded, members of the UN were also Omer Pasha Vrioni, Ndoc Pistulli, Refik Totani, Ndoc Ã‡oba, Sotir Peci and Xhafer Ypi. Fan Noli and Ahmet Zogu also performed the function of the chairman of KN.